UNSUR-UNSUR APORIA DALAM NASKAH DRAMA MEGA-MEGA KARYA ARIFIN C. NOER (SUATU PENDEKATAN DEKONSTRUKSI JACQUES DERRIDA) - H. Bogodad, Hardiyansa; Juanda, Juanda; Hajrah, Hajrah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2022)
This study aims to reveal the elements of aporia contained in the play Mega-Mega by Arifin C. Noer. The type of research used is descriptive qualitative. The results of this study indicate that there is a reversal of the domination of the characters in the text which is influenced by four forms of binary opposition reading, namely character, attitude, story, and status. The characters of the two different characters, namely Mae and Retno in the drama script, which include affection and selfishness are reversed by identifying the element of aporia. In conclusion, reading the meaning of the paradox or element of aporia in a text proves the opposite fact from what is built in the play's script.